A genetic study of von Recklinghausen neurofibromatosis in south east Wales. I. Prevalence, fitness, mutation rate, and effect of parental transmission on severity. Issue 11 (November 1989) - Huson, S M; Compston, D A; Clark, P; Harper, P S
Abstract : A population based study of von Recklinghausen neurofibromatosis in south east Wales (population 668, 100) identified 69 families with 135 affected members (prevalence 1/4950 of the population). In these families penetrance of the NF-1 gene was 100% by the age of five years. The genetic fitness of NF-1 sufferers was found to be reduced to 0.47, the effect being more marked in males than females (f = 0.31 and 0.60, respectively). Forty-one of 135 cases were judged to represent new disease mutations and the mutation rate was estimated to lie between 3.1 x 10(-5) and 10.4 x 10(-5). A parental age effect for new mutations was not found, nor was a maternal effect on disease severity.